Corporate Responsibility for Digital Content Piracy and Its Implications for Business Governance in Indonesia - Batubara, Ramot Hasudungan; Dirgantara, Febrian; Putra, Arif Rachman (Journal of Social Science Studies, 2024)
The digital era brings new challenges for intellectual property rights (IPR) protection, particularly in relation to digital content piracy. Corporate responsibility is not limited to the ownership of valid licenses, but extends to governance, prevention, detection, and mitigation of IPR violations across the entire service ecosystem. Indonesian law imposes civil, criminal, and administrative sanctions as the basis for corporate accountability, integrating copyright regimes, civil contracts, and electronic governance. The normative implications of this accountability compel companies to build an active compliance architecture, establish a zero-tolerance policy towards pirated content, and combine contractual controls, detection technology, and cross-authority collaboration. Responsive governance not only reduces the risk of sanctions but also enhances the competitiveness and credibility of digital businesses in Indonesia.